The hVps34‐SGK3 pathway alleviates sustained PI3K/Akt inhibition by stimulating mTORC1 and tumour growth. (17th October 2016) - Bago, Ruzica; Sommer, Eeva; Castel, Pau; Crafter, Claire; Bailey, Fiona P; Shpiro, Natalia; Baselga, José; Cross, Darren; Eyers, Patrick A; Alessi, Dario R
Abstract :